PRECISION AND ACCURACY ANALYSIS OF THE BIO SYSTEM MODEL A15 CLINICAL CHEMISTRY ANALIZER IN GLUCOSE MEASUREMENT - Al Vitto Marcelino Marcelino; Nur Hadziqoh (LPPM POLBITRADA, 2025)
Blood glucose examination is one of the methods for diagnosing diabetes. Many people experience delays in glucose testing due to concerns about the accuracy of the testing equipment. To produce high-quality results, clinical laboratories require testing equipment with high accuracy and precision. This study aimed to evaluate the precision and accuracy of the A15 clinical chemistry analyzer in measuring glucose parameters. This was a quantitative descriptive study, involving 30 samples and calculating the precision using the coefficient of variation (CV) formula and accuracy using the d% formula. The results showed that the obtained CV value was 4.93%, below the maximum tolerance limit set by the Indonesian Minister of Health Regulation No. 43 of 2013, which is 5%. The obtained d% value was -0.036, indicating a high level of accuracy. It can be concluded that the A15 clinical chemistry analyzer has good precision and accuracy in measuring blood glucose.